Ricotia candiriana (Brassicaceae), a new species from southern Anatolia, Turkey - Özçandir, Ayşen; Aykurt, Candan; Özüdoğru, Bariş (Phytotaxa, 2019)
Ricotia candiriana, from Alakır Valley (Kumluca, Antalya) in southern Anatolia (Turkey), is described as a new species and compared with its related species (R. davisiana). Its phylogenetic relationships within the genus are provided based on the nuclear-encoded ribosomal internal transcribed spacer (ITS) region. The International Union for Conservation of Nature (IUCN) threat category and observations on the ecology of the population are noted. The seed micromorphology of R. candiriana was examined using a scanning electron microscope and compared with R. davisiana.